The Impact of Formal Institutions on Public Sector Efficiency: Evidence from Environmental and Healthcare Performance - Alqasimi, Salem Abdulrahman; Zervopoulos, Panagiotis D.; Sharker, Abu Elias; Alshehhi, Jawahir M. (International Journal of Energy Economics and Policy, 2025)
This study investigates the impact of formal institutional factors on public sector efficiency, focusing on environmental and healthcare performance—two of the most widely examined sectors in the public administration literature. The empirical analysis is based on a panel of 139 countries—33 developed and 106 developing—covering the period from 2012 to 2020. The analysis adopts a three-stage methodological framework comprising: (a) Bayesian Data Envelopment Analysis (DEA) to estimate efficiency scores, (b) Principal Component Analysis (PCA) to construct a composite Public Sector Efficiency Index, and (c) a two-step Generalized Method of Moments (GMM) approach to evaluate the influence of institutional variables, country classification (developed vs. developing), and their interactions on public sector efficiency. The findings highlight the importance of sustained efforts to reduce CO₂ emissions and manage healthcare expenditures effectively. The results underscore the critical role of strengthening formal institutions and enhancing the Human Development Index (HDI) to improve public sector efficiency.